FRI0008 Mobilization of Lymphatic Endothelial Precursors Cells and Lymphatic Neovascularization in Primary Sjögren's Syndrome. (15th July 2016) - Alunno, A.; Manetti, M.; Bistoni, O.; Ibba Manneschi, L.; Rosa, I.; Caterbi, S.; Gerli, R.
Abstract : Background: Lymphatic neovascularisation is a key feature of chronic inflammation but is almost unexplored in primary Sjögren's syndrome (pSS). The two available studies that focused on lymphatic neovascularization in pSS minor salivary glands (MSGs) were limited to the assessment of glandular mature lymphatic endothelial cells and yielded conflicting results. A recent study in an experimental model of inflammation revealed that the pro-inflammatory cytokine IL-17 also displays a pro-lymphangiogenic function. IL-17 is a leading actor in the pathogenesis of pSS as it is involved in several steps of disease development and perpetuation Objectives: On this basis, aims of this study were: i. investigation of lymphangiogenic mediators and characterization of lymphatic vasculature in pSS; ii. Identification of the possible association of IL-17 and lymphatic neovascularization in this disease. Methods: Circulating lymphatic endothelial precursor cells (LEPCs) and Th17 cells were enumerated in 15 pSS and 15 healthy females. VEGF-C and IL-17 were assessed in paired serum samples by ELISA. Lymphatic vasculature, VEGF-C, VEGFR3 and IL-17 were evaluated by either immunofluorescence or immunohistochemistry in MSGs from 18 pSS MSGs compared to 8 non-specific chronic sialadenitis (NSCS) MSGs and 8 normal MSGs. Results: Circulating LEPCs were increased in pSS (p<0.0001) and were directly correlated to Th17 cell percentage, serum IL-17 and serum VEGF-C concentration (Spearman's rho=0.6; 0.6 and 0.5 respectively, all p<0.05). In pSS MSGs, a newly formed lymphatic capillary network was found within periductal inflammatory foci and the number of lymphatic vessels within the interlobular connective tissue was significantly increased compared to normal and NSCS MSGs (p<0.05). A strong expression of VEGF-C was detected in pSS ductal epithelial cells, microvessels and periductal inflammatory cells, while VEGF-C was barely detectable in ductal epithelial cells and microvessels of normal and NSCS MSGs. The expression of VEGFR-3 was strongly increased in lymphatic capillaries of pSS MSGs with respect to normal and NSCS MSGs. Numerous VEGFR-3 + infiltrating mononuclear cells were exclusively observed in pSS MSGs. IL-17 + inflammatory cells were often observed closely to lymphatic vessels in pSS MSGs, while no IL-17 expression could be detected in normal or NSCS MSGs. Conclusions: In this study, we investigated for the first time lymphvasculogenesis and lymphangiogenic mediators in pSS and demonstrated that they are associated to IL-17 axis in this disease. In addition, we reported increased and anatomically aberrant lymphatic neovascularization in pSS-MSGs. Our results suggest another pathogenic role of IL-17 in pSS, further supporting its therapeutic targeting in this disorder. References: Alunno A et al. Ann Rheum Dis 2013;72(2):286–92 Alunno A et al. J Autoimmun 2014;51:38–43 Chauhan SK et al. Blood 2011;118:4630–4634 Alunno A et al. Autoimmun Rev 2014;13(12):1167–1173 Disclosure of Interest: None declared